Peer Conformity, Drug Abuse Intentions, and Gender Against Drug Abuse Behavior in Adolescents in Tebo Ilir District, Jambi - Ridha Sirly; Elli Nur Hayati; Triantoro Safaria (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the effect of conformity, intention, and gender toward drug abuse behavior in Tebo Ilir Jambi District. The subjects of this study were 360 adolescents aged 15-21 years old, who live in Tebo Ilir District, Tebo Regency, Jambi Province. The data analysis in this study used multiple linear regression with the dummy method of the SPPS 26.0 for windows application. The hypothesis proposed is conformity, intention, and the influence of gender on drug abuse behavior. The results of this study indicate that conformity, intention, and gender affect drug abuse behavior with an R Square value of 0.752 with a significance value of (p= 0,000 <0,05). In addition, conformity has significant positive role toward drug abuse behavior (p= 0,000< 0,05), intention has significant positive role toward drug abuse behavior (p= 0,000< 0,05) and gender has significant positive role toward drug abuse behavior (p= 0,000<0,05). The male was involved in drug abuse behavior higher than the female with a mean value of 24.27, while the female was 12.39. Drug abuse behavior in adolescents is included in the moderate category with 296 adolescents out of 360 adolescents. The next result stated that 64 teenagers were in the highest category. This means that from 360 research respondents tend to use drugs.